Determinants of Physical Activity and Sedentary Behavior in German Elementary School Physical Education Lessons - David Jaitner; Michael Bergmann; Michael Bergmann; Arvid Kuritz; Christoph Mall; Filip Mess (Frontiers Media S.A., 2020)
Physical activity (PA) in school physical education (PE) is a signature component of health promotion and health education. The study's aim was to explore PA levels and sedentary time in German elementary school PE lessons and relate them to selected personal and environmental PA determinants. Accelerometer measurements were collected from 328 students (47% male, mean age 8.7 ± 1.2 years) in 11 elementary schools in Baden-Wuerttemberg (Germany). PA levels and sedentary time were analyzed regarding gender, grade, body mass index, selected correlates of active living and health behaviors, as well as the PE teachers' PE education status. In line with previous research, the analyses of PA levels and sedentary time confirm gender and grade differences and highlight older girls as the less active group. Deviant weight status and parents' PA levels were found to be important determinants for PA levels and sedentary time of girls and offer starting points for intervention studies as well as gender-appropriate PE in elementary schools. Specialist PE teacher status proved to be a negative determinant of PA levels and sedentary time for boys and girls and should be investigated in further studies, especially regarding the didactic and methodological background.